Study of Mortality of Eucalyptus Plantations in the Mahi Ravines, Central Gujarat - Verma, Balvir; Singh, Bakshish; Patel, A P (Annals of Arid Zone, 2016)
Experimental plantations of Eucalyptus camaldulensisDehn., (Bangalore) and Eucalyptus hybrid (Syn. Eucalyptustereticornis Sm., Bangalore) were raised in 1963 on the sandyalluvium of ravine lands along the Mahi river at the farmof Soil Conservation Research, Demonstration and TrainingCentre, Vasad (Gujar&t). The plantations indicated stuntedgrowth in 1965, and some trees started dying after growingto a height of 5-6 meters. Symptoms of chlorosis developedin the leaves of affected trees. Factors like rainfall, soilmoisture, soil analysis and leaf analysis have been discussedin the context of the above performance of the plantations.The soil was also examined for the presence of any pathogenson the roots of the dying trees and in the associated rootzone. The plantation has suffered due to soil moisture deficiencyand lime induced chlorosis of the leaves.